Peran Relasi Teman Sebaya dalam Membentuk Pengalaman Bullying di SDN Klampok Arum Kecamatan Tekung - Mu'taminah Mu'taminah (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
This qualitative study employing a case study method aimed to deeply understand the role of peer relationships in shaping bullying experiences at SDN Klampok Arum, Tekung Subdistrict. Data were collected through semi-structured interviews with students, teachers, and parents, as well as observations in the school environment. Data analysis was conducted using thematic analysis techniques. The research findings indicate that peer group norms, particularly those established by group leaders, can initiate and perpetuate bullying behavior. Peer support proved to be a protective factor for victims, while the role of bystanders significantly determined the continuation or cessation of bullying. In conclusion, the dynamics of peer relationships have a significant influence in shaping students' bullying experiences, thus anti- bullying interventions need to consider this social aspect.